Training For Selection of Internet of Things Devices as A Media For Remote Information Sender For Vocational School Teachers and Students - Dede Irawan Saputra; Hajiar Yuliana; Fauzia Haz; Giri Angga Setia; Dede Furqon Nurjaman; Naftalin Winanti; Irvan Budiawan (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Selection of devices for IoT needs can be determined based on the range from the shortest to the furthest, and on the internet access or Wi-Fi availability, which can be considered in advance and adjusted to the needs. In line with this, a training was carried out at SMKN 1 Cimahi, involving several groups of experts in the Electrical Engineering familyto open insight and understanding regarding the needs of devices that can be used to build internet-based or IoT systems. This training also introduced several observation schemes with various platforms, that are available in both free and paid choices. The training activities were carried out for 16 hours face-to-face, and 16 hours of independent projects that consisted of 10 modules. Out of these activities, it is expected that the participants can improve their thinking skills and carry out system programming processes according to needs and readiness.